Association between the promoter region of serotonin transporter polymorphisms and recurrent aphthous stomatitis: A meta-analysis. (January 2020) - Lu, Yuanyuan; Wang, Wenbing; Ding, Xianhui; Shi, Xiaolei
Highlights: RAS is the most common acute oral ulcerative disorder. 5-HTTLPR polymorphism may be associated with RAS occurrence. This meta-analysis supported the association between 5-HTTLPR and RAS. Abstract: Objectives: To assess the association between the promoter region of serotonin transporter (5-HTTLPR) gene polymorphism and recurrent aphthous stomatitis (RAS) occurrence. Designs: We performed the meta-analysis to determine the potential association between 5-HTTLPR polymorphism and RAS. We retrieved revelant studies from the PubMed, Scopus, Embase, Web of Science and Cochrane Library databases up to January 2019. Data were analyzed for odd ratios with 95% confidence intervals using Revman 5.3 software. Results: There were 4 studies in the meta-analysis, which included 291 RAS cases and 286 controls. It indicated a substantially augmented threat of RAS with respect to S vs. L ( P  =  0.005), SS vs. LL+LS ( P  ＜ 0.0001) and SS vs. LL models ( P  ＜ 0.00001), respectively. No heterogeneity was found between studies in all comparisons. Conclusions: The current meta-analysis provides evidence to prove the association between 5-HTTLPR polymorphism and RAS. Further studies should be performed to clarify the biochemical function and pathological role of 5-HTTLPR in the risk of RAS.